1973
DOI: 10.1037/h0034227
|View full text |Cite
|
Sign up to set email alerts
|

Contrast effects of background factors on the similarity-attraction relationship.

Abstract: This study tested the effects of exposure to a (first) bogus stranger exhibiting one of three different degrees of attitude similarity (.90, .50, or .10) on perceived similarity and attraction to a second stranger expressing a medium (.50) degree of attitude similarity. Perceived similarity and attraction to the second stranger were inversely related to the degree of attitude similartiy of the first stranger experienced by the subjects. The findings confirmed the adaptation-level prediction of "perceptual cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Experiments by Mascaro and Graves (1973) and Griffitt (1971) support the notion of a contrast effect within the attitude similarityattraction paradigm. Mascaro and Graves (1973) found that a second stranger's attraction was affected by the first stranger's rate of agreement. 1 That is, the second stranger was liked less as the first stranger's rate of agreement increased relative to that of the second stranger.…”
Section: Opposing Predictionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Experiments by Mascaro and Graves (1973) and Griffitt (1971) support the notion of a contrast effect within the attitude similarityattraction paradigm. Mascaro and Graves (1973) found that a second stranger's attraction was affected by the first stranger's rate of agreement. 1 That is, the second stranger was liked less as the first stranger's rate of agreement increased relative to that of the second stranger.…”
Section: Opposing Predictionsmentioning
confidence: 88%
“…In contrast, Stranger B should be liked more after the second meeting, since not only has the rate of agreement increased but the rate has also increased relative to that of Stranger A. Experiments by Mascaro and Graves (1973) and Griffitt (1971) support the notion of a contrast effect within the attitude similarityattraction paradigm. Mascaro and Graves (1973) found that a second stranger's attraction was affected by the first stranger's rate of agreement.…”
Section: Opposing Predictionsmentioning
confidence: 97%
“…A particular social stereotype may be an asset to a person in one situation, but a liability in another (Dermer & Thiel, 1975). Thus, initial attraction for a particular person should vary not only vdth stereotyped expectancies about that person, but also with the situational context of attraction judgments (Berscheid, Brothen, & Graziano, 1976;Berscheid & Graziano, in press;Mascaro & Graves, 1973;Wagner, 1975). If a person is expected to be aggressive, competitive, and dominant, for example, he may be perceived to be ideal for a business executive position; the expectation of the same qualities in an informal social situation might be met with less enthusiasm.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this prediction is consistent with a number of previously reported findings. Mascaro and Graves (1973) observed that the same target person was perceived to be more similar to a judge when that judge had previously been exposed to an extremely dissimilar person rather than to a person who was highly similar. Hensley and Duval (1976) found that a similar manipulation across five conditions affected judges' perception of their liking for a judged target group (group S ) as well as the perceived correctness of that groups' views.…”
Section: Self-categorization Theorymentioning
confidence: 95%